2008
DOI: 10.2215/cjn.01290308
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Infections among Patients with Chronic Kidney Disease

Abstract: The objectives of this review were (1) to review recent literature on the rates, risk factors, and outcomes of infections in patients who had chronic kidney disease (CKD) and did or did not require renal replacement therapy; (2) to review literature on the efficacy and use of selected vaccines for patients with CKD; and (3) to outline a research framework for examining key issues regarding infections in patients with CKD. Infection-related hospitalizations contribute substantially to excess morbidity and morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
185
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(193 citation statements)
references
References 52 publications
6
185
2
Order By: Relevance
“…25 The association between end-stage renal disease requiring dialysis and increased risk for infection is well established. 26,27 Uremia has been shown to depress the immune system, and patients undergoing chronic hemodialysis may have higher rates of colonization by potential pathogens such as methicillin-resistant Staphylococcus aureus. 28 We found a significant interaction between patient age, frequency of SSI, and 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…25 The association between end-stage renal disease requiring dialysis and increased risk for infection is well established. 26,27 Uremia has been shown to depress the immune system, and patients undergoing chronic hemodialysis may have higher rates of colonization by potential pathogens such as methicillin-resistant Staphylococcus aureus. 28 We found a significant interaction between patient age, frequency of SSI, and 30-day mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary immunodeficiency could be due to multiple reasons, e.g., profound metabolic disturbances and malnutrition due to uremia, as well as the immunosuppressive effect of hemodialysis in chronic renal failure (9,18), impaired respiratory function, chronic inflammation, and therapy with corticosteroids in COPD (8,42) or metabolic disorders and associated obesity in type 2 diabetes mellitus (16). The lowest anti-Hib immunity was detected in myeloma patients, likely caused by a decreased synthesis of normal immunoglobulins due to both malignant transformation of plasma cells and the immunosuppressive effect of chemotherapy (30).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown defects in neutrophil function, antigen processing, antibody formation, and cell-mediated immune responses in patients with CKD (25)(26)(27), and hyporesponsiveness to several vaccines have been described in children with CKD (9)(10)(11)(12)(13)(14)(15)(16). However, other vaccines in patients with CKD, such as varicella (28,29), have shown responses similar to those in the general population.…”
mentioning
confidence: 99%